Prenatal programming-effects on blood pressure and renal function - Ritz, Eberhard; Amann, Kerstin; Koleganova, Nadezda; Benz, Kerstin (Nature reviews. Nephrology, 2011)
Disturbed intrauterine organogenesis has long-term consequences on organ function in adulthood, so-called prenatal programming. In this Review, Ritz and colleagues outline the concept of prenatal programming and, in particular, describe its role in kidney disease and hypertension. Intrauterine growth restriction (IUGR) as a predictor of renal and cardiovascular disease in adulthood, and the potential of low birthweight as a (clinical) surrogate marker of IUGR, are also discussed.
Gesehen am 16.09.2022